2016
DOI: 10.1590/0104-07072016000040014
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Ambulatory: Weaknesses Pointed Out by Professionals

Abstract: The aim of this study was to identify the weaknesses of the mental health ambulatory service from the professionals' perspective. This was a qualitative study, developed by the Fourth Generation Evaluation method. Data were collected during February and March 2013 with the use of non-participant observation, individual opened interviews and group technique for the negotiation session. The informants were 12 working professionals at the ambulatory. The results pointed out weaknesses in the organizational struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
3
0
4
Order By: Relevance
“…These findings are in agreement with a research conducted in a mental health outpatient clinic, which showed deficient communication among the professionals and highlighted the absence of meetings at the service and the lack of internal communication, elements that, if present, could favor communication and exchange of information. 34 In a study conducted in a mental health service, it was found that the benefits of a family group were the following: a reduction in the participants' feeling of isolation; the strengthening of the sense 10/15 of a collective experience; the feeling of being heard; the reduction of stigma and shame; in addition to an increase in knowledge about mental illness and improved support skills directed to the person cared for. 7 This supports the results of this study, as the family members suggest more meetings and guidance as strategies to enable communication.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with a research conducted in a mental health outpatient clinic, which showed deficient communication among the professionals and highlighted the absence of meetings at the service and the lack of internal communication, elements that, if present, could favor communication and exchange of information. 34 In a study conducted in a mental health service, it was found that the benefits of a family group were the following: a reduction in the participants' feeling of isolation; the strengthening of the sense 10/15 of a collective experience; the feeling of being heard; the reduction of stigma and shame; in addition to an increase in knowledge about mental illness and improved support skills directed to the person cared for. 7 This supports the results of this study, as the family members suggest more meetings and guidance as strategies to enable communication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies point to the lack of professional training and permanent education, not only for BHU teams, but also for specialized services. [27][28] Despite the important local initiatives for professional training, they still do not meet professionals' needs with regard to developing mental health care in PHC. Thus, a major challenge is the redefinition of the work process, so that the influence of the biomedical model still persists today, both in professional…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente, algumas alterações à Portaria de consolidação da Raps foram realizadas, sendo incluída a Equipe Multiprofissional de Atenção Especializada em Saúde Mental/Unidades Ambulatoriais Especializadas como mais um dispositivo da rede (Portaria nº 3.588, 2017). Observamos a forma vasta como o serviço ambulatorial é referido nessa Portaria e principalmente em Portarias anteriores, o que propicia diversidade de modelos implantados pelo Brasil, mesmo antes de sua regulamentação (Guimarães, Oliveira, & Yamamoto, 2013;Paiano, Maftum, Haddad, & Marcon, 2016).…”
Section: Introductionunclassified
“…Independentemente da modalidade ofertada, individual ou em grupo, sua especificidade é o tratamento psicoterápico para quem está em situação de sofrimento psíquico, levando em conta, sobretudo, o viés clínico (Damous & Erlich, 2017). Paiano et al (2016) procuraram identificar em seu estudo as fragilidades do serviço ambulatorial de um município do noroeste do Paraná pela perspectiva de seus profissionais. Os resultados apontaram que, entre as fragilidades do serviço, havia dificuldade de acesso pelos usuários ao ambulatório e desconhecimento sobre as competências do local.…”
Section: Introductionunclassified